An Analysis of the legal framework governing disaster management in Kenya - Langat, Sharon Cheptoo (Strathmore University, 2016)
This study sought to examine the legal framework governing disaster management in Kenya. The study appreciates the gravity of disasters and the need for legislation of disaster management activities, in a bid to curb and reduce the effect of disasters, in the event that they occur. The objective of the study was to establish the extent to which a functioning legal framework for disaster management adequately facilitates the management of disaster. The study finds that a good legal framework, could go a long way in effectively managing disaster. Looking at the Disaster Management Act, 2002 (South Africa) , the study observes that some of its provisions are key to ensure a functioning system, such as the express allocation of funds to be used in disasters and the establishment of key bodies, vital in managing disasters. The study then proposes a National Disaster Management Bill for drafting and assent for use in Kenya.
A Dissertation submitted in partial fulfillment of the requirements for the award of the degree of bachelor of Laws (LL.B) at Strathmore University